Manifesto for new directions in developmental science. Issue 172 (22nd September 2020) - Barbot, Baptiste; Hein, Sascha; Trentacosta, Christopher; Beckmann, Jens F.; Bick, Johanna; Crocetti, Elisabetta; Liu, Yangyang; Rao, Sylvia Fernandez; Liew, Jeffrey; Overbeek, Geertjan; Ponguta, Liliana A.; Scheithauer, Herbert; et al.
Abstract: Although developmental science has always been evolving, these times of fast‐paced and profound social and scientific changes easily lead to disorienting fragmentation rather than coherent scientific advances. What directions should developmental science pursue to meaningfully address real‐world problems that impact human development throughout the lifespan? What conceptual or policy shifts are needed to steer the field in these directions? The present manifesto is proposed by a group of scholars from various disciplines and perspectives within developmental science to spark conversations and action plans in response to these questions. After highlighting four critical content domains that merit concentrated and often urgent research efforts, two issues regarding "how" we do developmental science and "what for" are outlined. This manifesto concludes with five proposals, calling for integrative, inclusive, transdisciplinary, transparent, and actionable developmental science. Specific recommendations, prospects, pitfalls, and challenges to reach this goal are discussed.